Growth optimization and organogenesis of Gerbera jamesonii Bolus ex. Hook f. in vitro - Hasbullah, N.A.; Taha, R.M.; Awal, A. (2008)
Regeneration potentials in Gerbera jamesonii Bolus ex. Hook f. from tissues culture system was studied using leaf, petiole and root explants. In vitro regeneration, callus induction and root formation were optimized by manipulation of growth regulators during organogenesis. Various kinds of plant growth regulators such as 6-Benzylaminopurine (BAP), Î±-Naphthalene acetic acid (NAA), 2, 4-Dichlorophenoxyacetic acid (2,4-D), Indole-3-acetic acid (IAA), Indole-3-Butyric acid (IBA), N6-2-Isopentenyl adenine (2iP), Kinetin and Zeatin were used to initiate cultures. These plant growth regulators were added to Murashige and Skoog medium in different combinations and concentrations. Adventitious shoots were obtained from petiole explants cultured on Murashige and Skoog (MS) medium supplemented with 2.0 mg L-1 BAP and 0.5 mg L-1 NAA. Effectiveness of shoot regeneration medium, type of growth regulator used and duration of induction period were investigated. Leaf explants cultured on MS medium supplemented with 1.0 mg L-1 BAP and 2.0 mg L-1 2, 4-D showed the best results for callus induction. Root explants were found to be non-regenerative in all experiments conducted. Petiole segment was identified as the best explant for regeneration of this species. Regenerated plants were rooted on Murashige and Skoog basal medium. Plantlets were then transferred to field with 75% survival rate. Â© 2008 Asian Network for Scientific Information.